Advances in Experimental Medicine and Biology
DOI: 10.1007/978-0-387-71767-8_13
|View full text |Cite
|
Sign up to set email alerts
|

The Exosporium of B.cereus Contains a Binding Site for gC1qR/p33: Implication in Spore Attachment and/or Entry

Abstract: B. cereus, is a member of a genus of aerobic, gram-positive, spore-forming rod-like bacilli, which includes the deadly, B. anthracis. Preliminary experiments have shown that gC1qR binds to B. cereus spores that have been attached to microtiter plates. The present studies were therefore undertaken, to examine if cell surface gC1qR plays a role in B. cereus spore attachment and/or entry. Monolayers of human colon carcinoma (Caco-2) and lung cells were grown to confluency on 6 mm coverslips in shell vials with ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Furthermore, C1q acted as a bridging molecule between BclA and integrin ␣ 2 ␤ 1 to mediate B. anthracis spore entry into epithelial cells in a complement activation-independent manner. A binding protein for the globular head domains of complement component C1q, designated gC1qR, was also reported to be involved in at least the initial stages of B. cereus spore attachment and/or entry (131).…”
Section: Functions Of the Exosporium In An Infected Hostmentioning
confidence: 99%
“…Furthermore, C1q acted as a bridging molecule between BclA and integrin ␣ 2 ␤ 1 to mediate B. anthracis spore entry into epithelial cells in a complement activation-independent manner. A binding protein for the globular head domains of complement component C1q, designated gC1qR, was also reported to be involved in at least the initial stages of B. cereus spore attachment and/or entry (131).…”
Section: Functions Of the Exosporium In An Infected Hostmentioning
confidence: 99%
“…In addition to these ligands, a number of bacterial and viral proteins have been identified that can bind either to surface-bound or intracellular p33 [28]. While the interactions of bacterial proteins with membrane-attached p33 is thought to promote cell adhesion and internalization of the pathogen [29,30,31], the interaction with viral proteins mainly takes place intracellularly and, in some cases, this has been shown to suppress virus replication [28]. Recently, we reported that p33 exhibits a high affinity for another group of proteins/peptides, namely AMPs.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, the C terminal domain of BclA (which is exposed at the spore surface) has high structural similarity to the portion of the complement protein C1q that binds antibody (Rety et al, 2005 ). Possible clues to the signifi cance of the structural similarity of BclA and C1q come from studies suggesting that B. cereus spores utilize the C1q receptor on lung and colon epithelial cells to facilitate attachment and entry of spores into the host (Ghebrehiwet et al, 2007 ). Perhaps, in the case of anthrax, interactions between BclA and C1q receptors on lung epithelial cells somehow facilitate phagocytosis by resident dendritic cells or alveolar macrophages.…”
Section: Functions Of the Exosporiummentioning
confidence: 99%